Woman and bioethics. Experiences and educative suggestions - Santa Cruz Vera, Dalia Jaqueline (2021)
The urgent demand for a more incisive presence of women in political, social, and cultural life has been made from different perspectives and diverse motivations. However, the specific contribution that only women can make could be frustrated when women's constitutive characteristics are neglected. Due to this risk, the educative l field is an important scenario to comprehend the feminine essence and to permeate the teaching practices. This article is the result of research and teaching of bioethics inserted in the curriculum of Humanities and Nursing. The purpose is to delve into the qualities of the authentic feminine to show what extent they could enrich the university educational praxis. The theoretical references are mainly the anthropological reflections of Edith Stein and John Paul II about women. The three traits that best represent the feminine nature were developed: interiority and openness, motherhood and care for life, strength and awareness of weakness; from which we offer some suggestions and educational experiences. In conclusion, the feminine genius, characterized by dedication and solidarity, can be evidenced in specific strategies that favor ethics and humanities teaching. It contributes to the development of a pro-life culture and a more deeply rooted social commitment to human dignity.